Students’ Anxiety in Learning English: A Case Study At the 4th Semester of the English Department of Muhammadiyah University, Sorong - Arniati, Fitri (CV Insan Kreasi Media, 2023)
Anxiety is a sense of restlessness, together with fear or worry, that may be mild or intense. Everyone has emotions of tension at some unspecified time in the future in their life. For example, you can experience involved and hectic approximately sitting an exam, or having a scientific test or job interview. Anxiety is a normal thing to feel when someone faces a situation or hears news that causes fear or worry. However, you need to be wary of anxiety if it appears for no reason or is difficult to control, because it could be caused by an anxiety disorder. This research aims to find out what elements are more likely to cause anxiety as felt by researchers in semester 4 of the English Department at Muhammadiyah University, Sorong. This research uses qualitative research techniques with a case study method. The setting of the study changed in the 4th semester of the English department of Sorong Muhammadiyah University. The study at carried out in the 4th semester of the English branch of Sorong Muhammadiyah University from April 14 to May 17, 2023. It consisted of interviews and more than one classroom observation for around a month in the 4th semester of the English branch of Sorong Muhammadiyah University. In collecting the data researcher uses interview and observation techniques. While analyzing data she reduces the data, displays and concludes. Based on the findings, the elements that contribute to anxiety might be categorized as follows: 1. Factors that Contribute to Anxiety come from Teacher (a). Speaking in front of the elegance. (b). Incomprehensible enter (c). Teachers’ character and attitude. 2. Factors that Contribute to Anxiety come from Students (a). Being laughed at with the aid of others (b). Students’ ideals about the language learning (c). Lack of education.